SOSIALISASI PENGENALANKEHIDUPAN KAMPUS BAGI MAHASISWA BARU (PPKMB) YAYASAN PENDIDIKAN NIAS SELATAN TAHUN 2021 - Darmawan Harefa; Samanoi Halowo Fau; Murnihati Sarumaha; Aluiwaauri Tafonao; Yurmanius Waruwu; Lies Dian Marsa Ndraha; Kristiurman Jaya Mendrofa; Mastawati Ndruru; Bestari Laia; Anita Zagoto; Agustinus Duha; Askarman Laia (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
Introduction to Campus Life for New Students (PKKMB) is a program that MUST be followed by all new students and is an activity to introduce and prepare new students in the process of becoming mature and independent students, accelerating the process of adjusting students to the new environment. environment and provide the tools for their success. college in the future. INTRODUCTION New Student Campus Life 2021 was attended by 386 students of the South Nias Education Foundation. After participating in the PKKMB, students must know and explain the Vision and Mission of the South Nias Education Foundation, be able to sing the Hymn and Mars of the South Nias Education Foundation. The values contained in this activity are as follows: a. Integrity b. Ethical c. Motivation, d. Power Analysis, e. Leadership, f. Confidence, g. friendly, h. Polite, I. Wise, j. Creative.